TEACHING CRITICAL THINKING IN BUSINESS ENGLISH FOR ACADEMIC PURPOSES - Karimov , Feruzjon Alisher o‘g‘li (GOLDEN BRAIN, 2024)
Critical thinking is a fundamental skill for students pursuing Business English for Academic Purposes (BEAP). This study examines the role of critical thinking in BEAP, exploring methods to enhance this skill and its impact on students’ academic and professional success. Through a mixed-methods approach, we investigate the effectiveness of specific pedagogical strategies in fostering critical thinking among BEAP learners. The quantitative survey conducted with 150 students revealed that while a majority recognize the importance of critical thinking, there is a significant gap in their confidence levels to apply these skills. Additionally, qualitative interviews with 20 instructors highlighted effective strategies such as case studies, group discussions, and reflective writing, along with challenges including language barriers and varying levels of prior knowledge. The study concludes that integrating targeted critical thinking activities into BEAP curricula and providing necessary support can significantly enhance students’ analytical abilities, preparing them for future academic and professional challenges.